The elements of ethics for professionals - Johnson, W. Brad; Ridley, Charles R (Palgrave Macmillan, 2008)
Patterned after Strunk and White's classic The Elements of Style, this handy reference concisely summarizes the substantial existing research on the delicate balance of professional ethics. Johnson and Ridley reduce the wealth of published material on the topic to the seventy-five most important and pithy truths for supervisors in all fields